The development of an inventory to measure high school students’ academic resilience in online learning - Wahyuni Wahyuni; Abdullah Pandang; Kulasse Kanto (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
This study aims to develop an inventory to measure the academic resilience of high school students in online learning. The research and development framework by Borg and Gall was employed to conduct this study. Results showed that: (1) the development of this inventory is highly needed by school counselors and students due to their lack of knowledge about the classifications of academic resilience that students may exhibit during online learning; (2) the inventory prototype is designed as a systematic guide in digital format, which includes discussions on academic resilience and online learning, as well as guidance on analyzing inventory data and delivering test results; and (3) the inventory has been rated highly for its validity and practicality by expert validators. The academic resilience indicator has a Cronbach’s alpha value of 0.821 for 41 items, and the online learning indicator has a Cronbach's alpha value of 0.845 for 33 items. Both values are greater than 0.70, indicating high reliability. Therefore, this inventory can be used as a testing instrument for guidance and counseling